1997
DOI: 10.1063/1.119051
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic magnetic coupling of permalloy micron dots forming a square lattice

Abstract: Static magnetic and spin wave properties of square lattices of permalloy micron dots with thicknesses of 500 Å and 1000 Å and with varying dot separations have been investigated. A magnetic fourfold anisotropy was found for the lattice with dot diameters of 1 µm and a dot separation of 0.1 µm. The anisotropy is attributed to an anisotropic dipole-dipole interaction between magnetically unsaturated parts of the dots. The anisotropy strength (order of 10 5 erg/cm 3 ) decreases with increasing in-plane applied ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
56
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(60 citation statements)
references
References 6 publications
2
56
2
Order By: Relevance
“…Last but not least, arrays of isolated magnetic dots are a good model system to study fundamental physical aspects of the next generation magnetic random access memory. Up to now there exist very few studies of magnetic dot arrays by BLS [6,7,8,28]. This is definitely connected to the fact that, on one hand, it is much more difficult to prepare dots with a well defined shape; and on the other hand, that the BLS cross section from dots is lower than that from wires simply due to the lower coverage of the surface by the magnetic material.…”
Section: Arrays Of Dotsmentioning
confidence: 91%
See 1 more Smart Citation
“…Last but not least, arrays of isolated magnetic dots are a good model system to study fundamental physical aspects of the next generation magnetic random access memory. Up to now there exist very few studies of magnetic dot arrays by BLS [6,7,8,28]. This is definitely connected to the fact that, on one hand, it is much more difficult to prepare dots with a well defined shape; and on the other hand, that the BLS cross section from dots is lower than that from wires simply due to the lower coverage of the surface by the magnetic material.…”
Section: Arrays Of Dotsmentioning
confidence: 91%
“…No inter-dot coupling was observed. Hillebrands et al [7,28] investigated spin wave properties of square lattices of micron-sized dots of permalloy with varying dot separations. Eight different samples comprising circular dots arranged in a 1x1 mm 2 square lattice with a diameter/periodicity of 1/1.1, 1/2, 2/2.2 and 2/4 µm, respectively, patterned into 500 and 1000 Å thick films were prepared.…”
Section: Arrays Of Dotsmentioning
confidence: 99%
“…On the other hand, Mathieu et al 26 found evidence for magnetostatic interaction between circular permalloy (Ni 80 Fe 20 ) dots with a diameter of 1 m on a square lattice with a 1.1 m period, while for the same type of dots with a 2 m period they found no magnetostatic interaction. Such studies are of current interest, since the magnetostatic interaction seems to strongly depend on the detailed structure of the system ͑dot material, shape, thickness, or type of array and center-tocenter or edge-to-edge distances͒.…”
mentioning
confidence: 99%
“…Although static properties and coupling phenomena in magnetic films patterned on the micron scale have been studied extensively [1,2,3,4], high-frequency dynamic properties of such films have been rarely investigated. On the other hand, the study of spin wave properties in conventional finite size systems is well established, such as the investigation of so-called Walker-modes in magnetic spheroids [5], and of dipolar-dominated surface modes (Damon-Eshbach modes) in finite-thickness slabs with infinite lateral dimensions [6].…”
mentioning
confidence: 99%